# Solve each problem #1.

QUESTION POSTED AT 15/01/2020 - 03:12 AM

QUESTION POSTED AT 15/01/2020 - 03:12 AM

15% = 15/100 = 15 out of a hundred. You answer is fifteen.

That would be C....x^2 - 7x + 6 = (x - 1)(x - 6)

ANSWERED AT 29/01/2020 - 05:40 PM

QUESTION POSTED AT 29/01/2020 - 05:40 PM

**Answer:**

**constant of variation is 10.**

**Second option is correct.**

**Step-by-step explanation:**

We have been given that y varies directly as x. Thus, we have

**y = kx.............(1)**

**k is the constant of variation**

Now, it has been given that when y is 12 then x is 1.2.

**Hence, substituting x = 1.2 and y = 12 in equation (1)**

12 = 1.2 k

**Divide both sides by 1.2**

k = 12/1.2

**k = 10**

**Therefore, constant of variation is 10.**

**Second option is correct.**

ANSWERED AT 29/01/2020 - 05:40 PM

QUESTION POSTED AT 29/01/2020 - 05:40 PM

-150x ≥ -2400

⁻¹⁵⁰ˣ/₋₁₅₀ ≥ ⁻²⁴⁰⁰/₋₁₅₀

x ≤ 16

-336 ≥ -21y

⁻³³⁶/₋₂₁ ≥ ⁻²¹/₋₂₁y

16 ≤ y

y ≥ 16

In the relation between x and y, x is always less than or equal to y. The answer is equal to C.

⁻¹⁵⁰ˣ/₋₁₅₀ ≥ ⁻²⁴⁰⁰/₋₁₅₀

x ≤ 16

-336 ≥ -21y

⁻³³⁶/₋₂₁ ≥ ⁻²¹/₋₂₁y

16 ≤ y

y ≥ 16

In the relation between x and y, x is always less than or equal to y. The answer is equal to C.

ANSWERED AT 29/01/2020 - 05:40 PM

QUESTION POSTED AT 29/01/2020 - 05:40 PM

10/5 = 1/x

cross multiply

10x = 5

x = 5/10

x = 1/2...u need 1/2 gallon per fish

cross multiply

10x = 5

x = 5/10

x = 1/2...u need 1/2 gallon per fish

ANSWERED AT 29/01/2020 - 05:40 PM

QUESTION POSTED AT 29/01/2020 - 05:40 PM

Start by combining like terms on both sides

-6+3=-3

Now we have:

To isolate g we need to subtract 12 from both sides -18-12= -30

Now we have

Divide both sides by -3 to isolate g, now we have:

When we divide an inequality by a negative we flip the sign so:

becomes:

Final answer:

ANSWERED AT 29/01/2020 - 05:38 PM

QUESTION POSTED AT 29/01/2020 - 05:38 PM

The domain is all the x values...so he domain is { 6,1,-3}

ANSWERED AT 29/01/2020 - 05:38 PM

QUESTION POSTED AT 29/01/2020 - 05:38 PM

(f + g)(x) = 3x^2 + 2x – 1

g(x) = 2x – 2

f(x) = ? ; 3x^2 + 1

Check by Substituting:

3x^2 + 1 + 2x - 2

Simplify:

3x^2 + 2x - 1

g(x) = 2x – 2

f(x) = ? ; 3x^2 + 1

Check by Substituting:

3x^2 + 1 + 2x - 2

Simplify:

3x^2 + 2x - 1

ANSWERED AT 29/01/2020 - 05:38 PM

QUESTION POSTED AT 29/01/2020 - 05:38 PM

2x + 7y = 4.....multiply by 2

-4x - 3y = 14

------------------

4x + 14y = 8 (result of multiplying by 2)

-4x - 3y = 14

----------------add

11y = 22

y = 2

2x + 7y = 4

2x + 7(2) = 4

2x + 14 = 4

2x = 4 - 14

2x = - 10

x = -5

solution is : (-5,2)

-4x - 3y = 14

------------------

4x + 14y = 8 (result of multiplying by 2)

-4x - 3y = 14

----------------add

11y = 22

y = 2

2x + 7y = 4

2x + 7(2) = 4

2x + 14 = 4

2x = 4 - 14

2x = - 10

x = -5

solution is : (-5,2)

ANSWERED AT 29/01/2020 - 05:36 PM

QUESTION POSTED AT 29/01/2020 - 05:36 PM

Multiply the value by 4 for the next value.

1:4 ratio

1:4 ratio

ANSWERED AT 29/01/2020 - 05:34 PM

QUESTION POSTED AT 29/01/2020 - 05:34 PM

**Answer:**

the first term is

**Step-by-step explanation:**

We have been given the polynomial

Arrange this polynomial in descending order. **In other words we arrange this polynomial having exponent from greatest to smallest.**

**Exponents from descending order is given by**

4, 3, 2, 0

**So, the polynomial when arranged in descending order is given by**

**Therefore, the first term is **

ANSWERED AT 29/01/2020 - 05:33 PM

QUESTION POSTED AT 29/01/2020 - 05:33 PM

The value of 'y' is 57.

ANSWERED AT 29/01/2020 - 05:32 PM

QUESTION POSTED AT 29/01/2020 - 05:32 PM

F(x) = 3x³ - 12x² - 15x

1) Factor Outside: 3x( x² - 4x - 5)

Factor Inside: 3x(x + 1)(x - 5)

2) Set Equal To 0:

3x = 0

x + 1 = 0

x - 5 = 0

3) Solve:

x = 0, -1, 5

1) Factor Outside: 3x( x² - 4x - 5)

Factor Inside: 3x(x + 1)(x - 5)

2) Set Equal To 0:

3x = 0

x + 1 = 0

x - 5 = 0

3) Solve:

x = 0, -1, 5

ANSWERED AT 29/01/2020 - 05:31 PM

QUESTION POSTED AT 29/01/2020 - 05:31 PM

Unit rate is the only one that makes logic sense

ANSWERED AT 29/01/2020 - 05:29 PM

QUESTION POSTED AT 29/01/2020 - 05:29 PM

F(x) = 3x + 1

let f(x) = y

y = 3x + 1

y - 1 = 3x

3x = y - 1

x = (y - 1)/3

From y = f(x), x = f⁻¹(y)

x = (y - 1)/3

f⁻¹(y) = (y - 1)/3

f⁻¹(7) = (7 - 1)/3 = 6/3 = 2

f⁻¹(7) = 2

let f(x) = y

y = 3x + 1

y - 1 = 3x

3x = y - 1

x = (y - 1)/3

From y = f(x), x = f⁻¹(y)

x = (y - 1)/3

f⁻¹(y) = (y - 1)/3

f⁻¹(7) = (7 - 1)/3 = 6/3 = 2

f⁻¹(7) = 2

ANSWERED AT 29/01/2020 - 05:28 PM

QUESTION POSTED AT 29/01/2020 - 05:28 PM

I'm going to have to say 10.5, because that side looks the same as the side with the number 9.

ANSWERED AT 29/01/2020 - 05:27 PM

QUESTION POSTED AT 29/01/2020 - 05:27 PM

i think its 11.45 rounded its 11.5 from what I found its this

ANSWERED AT 29/01/2020 - 05:25 PM

QUESTION POSTED AT 29/01/2020 - 05:25 PM

Solve for k for each value of the range, and you will obtain each value of k that may belong to the domain

1) k^2 +2k +1 = 25

k^2 + 2k -24 = 0

(k + 6)(k- 4) = 0

k + 6 = 0 ⇒ k = - 6

k - 4 = 0 ⇒ k = 4

2) k^2 + 2k + 1 = 64

k^2 + 2k - 63 = 0

(k + 9)(k - 7) = 0

k + 9 = 0 ⇒ k = -9

k - 7 = 0 ⇒ k = 7

Then the largest possible domain is {-9, -6, 4, 7}

You might exclude one from -6 and 4 but not both.

You might also exclude one from -9 and 7 but not both

Because with those sets you will obtain all the images that are in the range.

1) k^2 +2k +1 = 25

k^2 + 2k -24 = 0

(k + 6)(k- 4) = 0

k + 6 = 0 ⇒ k = - 6

k - 4 = 0 ⇒ k = 4

2) k^2 + 2k + 1 = 64

k^2 + 2k - 63 = 0

(k + 9)(k - 7) = 0

k + 9 = 0 ⇒ k = -9

k - 7 = 0 ⇒ k = 7

Then the largest possible domain is {-9, -6, 4, 7}

You might exclude one from -6 and 4 but not both.

You might also exclude one from -9 and 7 but not both

Because with those sets you will obtain all the images that are in the range.

ANSWERED AT 29/01/2020 - 05:23 PM

QUESTION POSTED AT 29/01/2020 - 05:23 PM

Are you sure the h is after the parentheses or are the after the 1/2

ANSWERED AT 29/01/2020 - 05:23 PM

QUESTION POSTED AT 29/01/2020 - 05:23 PM

Weeks : 1 2 3 4 5

number of insects : 4 8 16 32 64

each week ur insect collection doubled...so by week 5, u had 64 insects in ur collection

number of insects : 4 8 16 32 64

each week ur insect collection doubled...so by week 5, u had 64 insects in ur collection

ANSWERED AT 29/01/2020 - 05:22 PM

QUESTION POSTED AT 29/01/2020 - 05:22 PM

Simplifying

3x + -4y = 16

Solving

3x + -4y = 16

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4y' to each side of the equation.

3x + -4y + 4y = 16 + 4y

Combine like terms: -4y + 4y = 0

3x + 0 = 16 + 4y

3x = 16 + 4y

Divide each side by '3'.

x = 5.333333333 + 1.333333333y

Simplifying

x = 5.333333333 + 1.333333333y

3x + -4y = 16

Solving

3x + -4y = 16

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4y' to each side of the equation.

3x + -4y + 4y = 16 + 4y

Combine like terms: -4y + 4y = 0

3x + 0 = 16 + 4y

3x = 16 + 4y

Divide each side by '3'.

x = 5.333333333 + 1.333333333y

Simplifying

x = 5.333333333 + 1.333333333y

ANSWERED AT 29/01/2020 - 05:22 PM

QUESTION POSTED AT 29/01/2020 - 05:22 PM

1: 1,000,000

Then you mark points 1, 2, 3, 4, 5, 6, 7, 8, 9 and 10 on the y-axis.

The origin is 0

1 is equivalent to 1,000,000

2 is 2,000,000

3 is 3,000,000 ...

and so on, until 10 which is 10,000,000

Then you mark points 1, 2, 3, 4, 5, 6, 7, 8, 9 and 10 on the y-axis.

The origin is 0

1 is equivalent to 1,000,000

2 is 2,000,000

3 is 3,000,000 ...

and so on, until 10 which is 10,000,000

ANSWERED AT 29/01/2020 - 05:21 PM

QUESTION POSTED AT 29/01/2020 - 05:21 PM

−19x+2y is the answer.

ANSWERED AT 29/01/2020 - 05:19 PM

QUESTION POSTED AT 29/01/2020 - 05:19 PM

Hint:

r_{y=k): (x,y)->(x,-(y-k)+k)

or simplified,

r_{y=k): (x,y)->(x,2k-y)

So in this case, k=-1, x=2, y=-4

(2,-4) -> (2, 2(-1)-(-4)

(2,-4) -> (2, -2+4)

(2,-4) -> (2, 2)

r_{y=k): (x,y)->(x,-(y-k)+k)

or simplified,

r_{y=k): (x,y)->(x,2k-y)

So in this case, k=-1, x=2, y=-4

(2,-4) -> (2, 2(-1)-(-4)

(2,-4) -> (2, -2+4)

(2,-4) -> (2, 2)

ANSWERED AT 29/01/2020 - 05:19 PM

QUESTION POSTED AT 29/01/2020 - 05:19 PM

Well, you technically didn't finish your question, but she would need to double the 1 1/8 cup of butter she already has. 0.75(3) is equal to 2.25. 1 1/8 converted to decimal form is 1.125, which is half of 2.25. Therefore, in a sense she would have to double the amount of butter she already has. Otherwise, she can only make 1.5 times of the recipe

ANSWERED AT 29/01/2020 - 05:18 PM

QUESTION POSTED AT 29/01/2020 - 05:18 PM

-3(y-5) = 24...distribute through the parenthesis

-3y + 15 = 24....subtract 15 from both sides

-3y = 24 - 15

-3y = 9...divide both sides by -3

y = 9/-3

y = -3

-3y + 15 = 24....subtract 15 from both sides

-3y = 24 - 15

-3y = 9...divide both sides by -3

y = 9/-3

y = -3

ANSWERED AT 29/01/2020 - 05:17 PM

QUESTION POSTED AT 29/01/2020 - 05:17 PM

I think the answer is 27a^3+8c^3 :) is this algebra??

ANSWERED AT 29/01/2020 - 05:17 PM

QUESTION POSTED AT 29/01/2020 - 05:17 PM

The coordinates of the image are : **C ) ( 2, 2 )**

ANSWERED AT 29/01/2020 - 05:17 PM

QUESTION POSTED AT 29/01/2020 - 05:17 PM

**Answer:**

The correct answer is **C.**

**Step-by-step explanation:**

Notice that the difference between consecutive values of x is always 1, and the difference between consecutive values of y is always 2. This means that

where and stands for two consecutive values of x, and the same goes to y.

Now, notice that this is the definition of the slope of the equation of a line. Then, a line can be characterized by this condition, and that is why **C ** is the correct answer.

Anyway, you can check that this set of point is generated by a linear function in other way. Suppose that it can be done, and the linear function has the form

.

From the pair (0,7) we deduce that , then . Now, substituting the pair (-3,1) we get and as consequence . Thus, if the points are generated by a linear function, its expression would be .

Now, substitute the different values of x and check that the same values of y are obtained.

ANSWERED AT 29/01/2020 - 05:16 PM

QUESTION POSTED AT 29/01/2020 - 05:16 PM

1. Equation of circle = (x - a)^2 + (y - b)^2 = r^2; where (a, b) is the centre of the circle and r is the diameter.

(x - (-5))^2 + (y - (-7))^2 = 6^2

(x + 5)^2 + (y + 7)^2 = 36

x^2 + 10x + 25 + y^2 + 14y + 49 = 36

x^2 + y^2 + 10x + 14y + 38 = 0

(x - (-5))^2 + (y - (-7))^2 = 6^2

(x + 5)^2 + (y + 7)^2 = 36

x^2 + 10x + 25 + y^2 + 14y + 49 = 36

x^2 + y^2 + 10x + 14y + 38 = 0

ANSWERED AT 29/01/2020 - 05:15 PM

QUESTION POSTED AT 29/01/2020 - 05:15 PM

**Answer:**

The correct option is B.

**Step-by-step explanation:**

It is given that the ordered pairs below represent a linear relation between x and y. (-3,0), (-2,4), (-1,8), (0,12), (1,16), (2,20).

At y-intercept the value of x is 0. From the given points we can say that the y-intercept of the function is (0,12).

If a line passing through the two points, then the slope of the function is

The slope of the function is

**Therefore the slope of the line represented by this table is 4 and the y-intercept is 12. Option B is correct.**

ANSWERED AT 29/01/2020 - 05:15 PM

QUESTION POSTED AT 29/01/2020 - 05:15 PM